Acceleration rate of mitral inflow E wave: a novel transmitral doppler index for assessing diastolic function. Issue 1 (December 2015) - Badkoubeh, Roya; Tavoosi, Anahita; Jabbari, Mostafa; Parsa, Amir; Geraeli, Babak; Saadat, Mohammad; Larti, Farnoosh; Meysamie, Ali; Salehi, Mehrdad
Abstract Background We performed comprehensive transmitral and pulmonary venous Doppler echocardiographic studies to devise a novel index of diastolic function. This is the first study to assess the utility of the acceleration rate (AR) of the E wave of mitral inflow as a primary diagnostic modality for assessing diastolic function. Methods Study group consisted of 84 patients (53 + 11 years) with left ventricle (LV) diastolic dysfunction and 34 healthy people (35 ± 9 years) as control group, who were referred for clinically indicated two-dimensional transthoracic echocardiogram (TTE) during 2012 and 2013 to Imam Hospital. Normal controls were defined as patients without clinical evidence of cardiac disease and had normal TTE. LV diastolic function was determined according to standardized protocol of American Society of Echocardiography (ASE). As our new parameter, AR of E wave of mitral inflow was also measured in all patients. It was represented by the slope of the line between onset of E wave and peak of it. Correlation between AR of E wave and LV diastolic function grade was measured using the Spearman correlation coefficient. Receiver operating characteristic (ROC) curve was used to determine the sensitivity and specificity of AR of E wave in diagnosing LV diastolic dysfunction in randomly selected two-thirds of population then its derived cutoff was evaluated in rest of the population. The institutional review board of the hospital approved the study protocol. All participants gave written informed consent. This investigation was in accordance with the Declaration of Helsinki. Results The mean value of AR was 1010 ± 420 cm/s2 in patients whereas the mean value for the normal controls was 701 ± 210 cm/s2 . There was a strong and graded relation between AR of E wave of mitral inflow and LV diastolic function grade (SpearmanP ≤0.0001, rs =0.69). ROC curve analysis revealed that AR of E wave of mitral inflow =750 cm/s2 predicted moderate or severe LV diastolic dysfunction with 89 % sensitivity and 89 % specificity (area under curve [AUC] = 0.903, P <0.0001). Application of this cutoff on test group showed 96 % sensitivity and 77 % specificity with AUC = 0.932 andP <0.0001. Conclusion AR of E wave of mitral inflow could be used for assessment of diastolic function, especially moderate or severe diastolic dysfunction. However, before its clinical application, external validation should be considered.